Fuel production from waste vehicle tires by catalytic pyrolysis and its application in a diesel engine - Ilkilic, Cumali; Aydin, Huseyin (Elsevier, 2011)
An alternative fuel production was performed by pyrolysis of waste vehicle tires under nitrogen (N-2) environment and with calcium hydroxide (Ca(OH)(2)) as catalyst. The sulfur content of liquids obtained were reduced by using Ca(OH)(2). The liquid fuel of waste vehicle tires(TF) was then used in a diesel engine to blend with petroleum diesel fuel by 5%(TF5), 10%(TF10), 15%(TF15), 25%(TF25), 35%(TF35), 50%(TF50). and 75% (TF75) wt. and pure (TF100). Performance characteristics such as engine power, engine torque, brake specific fuel consumption (bsfc) and exhaust temperature and emission parameters such as oxides of nitrogen (NOx), carbon monoxides (CO), total unburned hydrocarbon (HC). sulfur dioxides (SO2) and smoke opacity of the engine operation with IF and blend fuels of TF-diesel were experimentally investigated and compared with those of petroleum diesel fuel. It was concluded that the blends of pyrolysis oil of waste tires TF5, TF10. TF25 and TF35 can efficiently be used in diesel engines without any engine modifications. However, the blends of TF50, TF75 and TF100 resulted considerably to high CO, HC, SO2 and smoke emissions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Pyrolysis; Vehicle tires; Tire fuel; Diesel engine